Zero-temperature quantum annealing bottlenecks in the spin-glass phase - Sergey Knysh (Nature Portfolio, 2016)
Quantum annealing can solve hard optimization problems, but it is limited by computational bottlenecks. Here, the author obtains the scaling of spin-glass bottlenecks with the problem size and explains a crossover to exponential complexity for large sizes.